2022
DOI: 10.2147/dhps.s363925
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Perceptions of Nurse Practitioners on Adverse Events Following Immunization and Barriers to Reporting in the Central Region, Eritrea: A Cross-Sectional Study

Abstract: Background Though vaccines are generally considered extremely safe and effective, they have been associated with some serious adverse events following immunization (AEFIs). AEFIs might be related to either the vaccine, immunization error, anxiety related to immunization, and/or coincidental events. If they are not reported and investigated in timely fashion, they can create rumors and confidence gaps. In the last few years, reporting AEFIs in the Central Region of Eritrea, compared to other region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
(9 reference statements)
1
0
0
Order By: Relevance
“…Poor counselling by the vaccinator regarding these adverse effects resulted in participants leaving the program. Similar findings were reported in a study which emphasized that injection neuritis could be prevented through proper injection techniques and vaccinators adopting aseptic injection practice [ 26 ].…”
Section: Discussionsupporting
confidence: 88%
“…Poor counselling by the vaccinator regarding these adverse effects resulted in participants leaving the program. Similar findings were reported in a study which emphasized that injection neuritis could be prevented through proper injection techniques and vaccinators adopting aseptic injection practice [ 26 ].…”
Section: Discussionsupporting
confidence: 88%
“…Other research looking at healthcare workers with regard to AEFI surveillance showed that the majority had 0-9 years' working experience. 14 Another study of healthcare professionals dealing with AEFI looked at the mean number of years working in a professional group as 19 years. 15 The most prevalent SOC that was affected by adverse events was "general disorders and administration site conditions" (89.6%).…”
Section: Discussionmentioning
confidence: 99%